2022
DOI: 10.1101/2022.10.31.514500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety margin evaluations for transtympanic laser stimulation of the cochlea from the outer ear in Mongolian gerbils (Meriones unguiculatus)

Abstract: Infrared laser stimulation of the cochlea has been proposed as a possible alternative to conventional auditory prostheses. The safety margin of laser stimulation must be determined for the practical application of the laser to a prosthesis. This study assessed the effect of laser-induced damage to the cochlea on auditory perception. To examine the effects of laser-induced injury of the auditory system on the perception of auditory stimuli, we trained Mongolian gerbils (Meriones unguiculatus) using a head-fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Our previous study demonstrated that a transtympanic laser at 6.6 W/cm 2 did not induce observable thermal elevation and did not cause histological, electrophysiological, or behavioral damage in Mongolian gerbils ( 11 ). Our current data show that a laser-evoked behavioral response started to be observed at approximately 1.1 mJ/cm 2 or more, with a pulsed laser train at 4000 Hz delivered for 500 ms (i.e., radiant energy of the stimulus was 2.2 W/cm 2 ), indicating that laser-evoked perception could be generated within a safety margin of the laser stimulation (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Our previous study demonstrated that a transtympanic laser at 6.6 W/cm 2 did not induce observable thermal elevation and did not cause histological, electrophysiological, or behavioral damage in Mongolian gerbils ( 11 ). Our current data show that a laser-evoked behavioral response started to be observed at approximately 1.1 mJ/cm 2 or more, with a pulsed laser train at 4000 Hz delivered for 500 ms (i.e., radiant energy of the stimulus was 2.2 W/cm 2 ), indicating that laser-evoked perception could be generated within a safety margin of the laser stimulation (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…After surgery, all subjects were individually housed and given a recovery period of at least two days before training commenced. The animal surgery followed the same procedure as in our previous studies ( 4, 5 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations